Prevalence and Correlates of Any and Frequent Synthetic Cannabinoid Use in a Representative Sample of High School Students. (28th July 2016) - Clements-Nolle, Kristen; Lensch, Taylor; Larson, Sandra; Yang, Wei
ABSTRACT: Background : There is increasing evidence that Synthetic Cannabinoid (SC) use is associated with adverse health effects, but little is known about the prevalence of SC use and risk and protective factors for SC use among adolescents. Objectives : To determine the prevalence and correlates of any and frequent SC use in a representative sample of high school students. Methods : The 2013 Youth Risk Behavior Survey was administered to 3, 928 high school students in Nevada. A state-added question assessed any and frequent SC use (10 or more times). Weighted logistic regression identified factors for both outcomes. Results : 17.3% of students reported SC use and 4.3% used SCs frequently. As expected, there were strong associations between SC use and other substance use. After controlling for substance use, any SC use was associated with being Hispanic (AOR = 1.74; 95% CI = 1.27, 2.38) and living in a rural county (AOR = 1.68; 95% CI = 1.26, 2.23). Frequent SC use was higher among students who were male (AOR = 2.14; 95% CI = 1.19, 3.84), 18 years of age (AOR = 2.34; 95% CI = 1.18, 4.67), lived in a rural county (AOR = 1.84; 95% CI = 1.11, 3.04), and were offered, sold, or given illegal drugs on school property (AOR = 2.40; 95% CI = 1.53, 3.79). Protective factors for frequent SC use included high parental monitoring (AOR = 0.54; 95% CI = 0.31, 0.93) and sports team participation (AOR = 0.61; 95% CI = 0.37, 0.99). Conclusions/Importance : SC prevention policies and programs should focus on adolescents who live in rural settings and engage in substance use. Initiatives to address drug availability as school and promote parent involvement are also warranted.